Intergenerational wealth mobility in rural Bangladesh - M. Niaz Asadullah (Institute for the Study of Labor (IZA), 2011)
Unique residential history data with retrospective information on parental assets are used to study household wealth mobility in 141 villages in rural Bangladesh. Regression estimates of father-son correlations and analyses of intergenerational transition matrices show substantial persistence in wealth even when we correct for measurement errors in parental wealth. We do not find wealth mobility to be higher between periods of a person's life than between generations. We find that the process of household division plays an important role: sons who splinter off from the father's household experience greater (albeit downward) mobility in wealth. Despite significant occupational mobility across generations, its contribution to wealth mobility, net of human capital attainment of individuals, appears insignificant. Low wealth mobility in our data is primarily explained by intergenerational persistence in educational attainment.
urn:nbn:de:101:1-20110927177
Keywords: D63; O53; 330; intergenerational inequality; household wealth; occupational mobility; schooling mobility; transition matrix; Bangladesh